Infantile Perianal Pyramidal Protrusion: A Report of 8 New Cases and a Review of the Literature - N. Zavras; E. Christianakis; S. Tsamoudaki; K. Velaoras (Case Reports in Dermatology, 2012)
Infantile perianal pyramidal protrusion (IPPP) is characterized by a protrusion located most often anterior to the anus. Three types of IPPPs are recognized: (a) constitutional, (b) acquired (mainly due to constipation), and (c) IPPPs due to lichen sclerosus et atrophicus. The aim of this study was to make a brief review on IPPPs from articles retrieved from PubMed, and to present our experience in this field. We conclude that awareness of pediatric surgeons and pediatricians of the condition is essential for the correct diagnosis of IPPP, and could help to avoid erroneous investigation of other lesions in this area.